(untitled) (Journal of Plant Disease Sciences, 2025)
Kodo millet ( L.) an ancient crop which is now getting very popularize due to its high nutritive values and health benefits. The crop is attacked by numerous diseases but one of the major limiting one is leaf blight known to be caused by Alternaria tenuissima and spp. Recently in the experiment, it was encountered that a new species of Bipolaris is causing leaf blight. A proper protocol regarding the identification was made using ITS 1 and ITS 4 primer pairs and then it was confirmed that pathogen responsible for it was . The submission was done to Genbankm and accession no. PP774224 was obtained. This revealed that the pathogen shared 99.20% similarity with other strains , MH201400, MF490805, KX452450 and OR220036, whereas it showed 98.18% similarity with KF725816 and 98.40% with JQ936104 used in phylogenetic analysis, respectively.